Successful Combination Therapy of Trazodone and Fluvoxamine for Pica in Alzheimer's Disease: A Case Report - Kanamori, Tadashi; Kaneko, Yoshiyuki; Yamada, Kouju; Suzuki, Masahiro (Frontiers in Psychiatry, 2021)
Pica in Alzheimer’s disease (AD) makes it difficult for caregivers to provide care. However, few effective medications have been reported for pica in AD. We report a case of AD with pica that was successfully improved by trazodone and fluvoxamine. An 80-year-old woman with AD was admitted to our hospital due to aggravated pica, including eating weeds in the facility’s garden and eating a dishwashing sponge. Her pica was accompanied by oral tendency, prosopagnosia, and placidity. She took rivastigmine and memantine, but these were ineffective for her pica. She was given olanzapine and perospirone, but both were discontinued due to over-sedation and severe extrapyramidal symptoms, respectively. We then administered trazodone and fluvoxamine, both of which have demonstrated effectiveness for pica in frontotemporal dementia (FTD). Her pica behaviors then disappeared without daytime sleepiness. In this case, pica with oral tendency, which was accompanied by prosopagnosia and placidity, may be interpreted as a partial symptom of Klüver−Bucy syndrome (KBS). KBS is often seen in FTD, but also occurs in late-stage AD. Our case together with previous reports showing that trazodone and fluvoxamine were effective for pica in FTD suggest that the same common drug therapy may be successful in pica with oral tendency, regardless of the subtype of dementia.